2019
DOI: 10.1038/s41598-019-47768-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating ruminal crude protein degradation from beef cattle feedstuff

Abstract: We estimated ruminal crude protein degradation of twelve feedstuffs commonly used in China using in vitro and in vivo methods. The in vivo net protein utilization (NPU) levels of corn, sorghum, barley, wheat, Chinese wild rye grass, corn stalk, rice straw, soybean straw, soybean meal, distillers’ dried grains with solubles (DDGS), Brewers’ spent grains, and sunflower meal were 52.57, 49.68, 65.38, 72.58, 82.41, 72.26, 68.57, 76.95, 54.75, 56.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…According to previous studies [14,15,49], the release rate of energy other than protein mattered in synchrony. In situ rumen degradation showed that the water-soluble and rapidly degradable protein fraction of soybean meal is about 27%, and the in vitro crude protein degradation rate of soybean meal can be up to 60% in the first 6 h of incubation [50][51][52]. Okeke et al (1983) also reported that the rumen NH 3 -N concentration was maximum at 0-6 h after feeding diets with soybean meal as the main protein source [53].…”
Section: Discussionmentioning
confidence: 98%
“…According to previous studies [14,15,49], the release rate of energy other than protein mattered in synchrony. In situ rumen degradation showed that the water-soluble and rapidly degradable protein fraction of soybean meal is about 27%, and the in vitro crude protein degradation rate of soybean meal can be up to 60% in the first 6 h of incubation [50][51][52]. Okeke et al (1983) also reported that the rumen NH 3 -N concentration was maximum at 0-6 h after feeding diets with soybean meal as the main protein source [53].…”
Section: Discussionmentioning
confidence: 98%
“…Protein is an essential nutrient that determines the economic success of the beef cattle industry (Chathurika et al 2019). The beef cattle rumen degrades low biological protein and low-quality fiber into a microbial protein with high biological value (Liu et al 2019;Chathurika et al 2019). Ammonia serves as a primary nitrogen source for most ruminal microbes (Imsya et al 2013), which is responsible for carrying out higher microbial protein synthesis (Supapong et al 2019;Mayulu et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of this element is employed to estimate protein degradation and usage by ruminal microbes; hence OMD has a strong correlation with microbial protein synthesis (Imsya et al 2013). N-NH 3 production reflects the amount of feedstuff protein degraded, and the rate at which this process occurs is an important characteristic for determining protein value (Liu et al 2019). Ammonia nitrogen is an essential nutrient in promoting microbial growth.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of ruminal fermentation kinetics, based on the France model, revealed a maximum gas production potential (A) and a shorter colonization time associated with the diet containing 0% of BMM in comparison to the other treatments (Table 3). The control diet was composed of only corn and soybean, as the main staples, which have high fermentability and, therefore, promote fast colonization by ruminal microorganisms (Cabral et al, 2002;Homem Júnior et al, 2019, Liu et al, 2019.…”
Section: Resultsmentioning
confidence: 99%